Penerapan Metode ORESTE dalam Menentukan Paket Internet yang Ideal di Kalangan Mahasiswa (Kasus Siantar-Simalungun) - Khadafi, Farhan; Wiratama, Firman Dwi; Aryaputra, Safa; Parinduri, Syawaluddin Kadafi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Choosing the ideal internet package is a challenge for students in the Siantar-Simalungun region. Stable and affordable internet access is essential to support various academic activities, ranging from literature searches and assignment collection to online learning activities. When choosing an internet package, students generally consider several key factors such as price, network speed, signal strength, bonus quotas, and user satisfaction levels. This study uses the ORESTE (Organization, Rangement Et Synthèse De Données Relationnelles Extérieures) method as a multi-criteria decision-making approach to determine the most ideal internet package for students' needs. The research data was collected through a questionnaire distributed to more than 1,217 students from various educational institutions in the region. Through the calculation and analysis process using the ORESTE method, it was found that Telkomsel was the most ideal internet package choice with the lowest preference value of 1.774, which indicates the highest level of preference compared to other alternatives. The results of this study are expected to serve as a reference in helping students choose the internet package that best suits their needs, thereby increasing the efficiency of internet spending while supporting productivity and smooth academic activities with optimal internet access.